Programming Teaching in the Era of Artificial Intelligence - Chien-Hsing Huang (Eximia, 2024)
With the development of science and technology, computer applications are changing with each passing day, changing our lives in all aspects. Computers have become an indispensable tool in life, and learning programming languages to operate computers has become a major focus of education. From low-level languages to high-level languages to visual programming languages, and finally to generative artificial intelligence to generate code. Program development tools are constantly updated as computers advance. This has the benefit of lowering barriers to learning, but also results in a weaker understanding of how the program works. This article designs a programming language learning strategy that combines the above programming development tools to lower the threshold for programming language learning and improve learning efficiency.